Multicultural Pentecostal Congregations: - D.N. Andrew; W.J. Schoeman; L.J.S. Botes (Acta Theologica)
The study investigates the extent of gender discrimination and prejudice in multicultural Pentecostal congregations and the potential for a future in which gifts and ministry contributions of women are foregrounded. Multicultural congregations were studied to explore the gifts that the ministry of women contributes to the work of the church and to the social cohesion of the congregation. This qualitative study collected data from men and women in five focus group discussions, with about 10 people in each group, held in five multicultural congregations. The data collected were analysed through the Atlas.ti program and findings were divided into themes that answered the question whether multicultural congregations create a space for the inclusion of the gifts and ministry of women.